Parametric Optimization for Automatic Control System of 300 MW Power Units at a Constant Steam Pressure Upstream of the Turbine - G. T. Kulakov; A. T. Kulakov; K. I. Artsiomenka (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The problem of parametric optimization of automatic control systems of power units (ACSPU) of 300 MW at the Lukoml’skaya GRES (Lukoml Condensing Power Plant) at a constant superheated steam pressure upstream of the turbine is under consideration. During 1974–1979, eight units of the Lukoml’skaya GRES implemented ACSPU with a leading boiler power control, which will be forced to work in a wide range of loads due to the planned commissioning of two power units of the Belarusian NPP: the first one – in 2019, and the second one – in 2020. The total capacity of the Belarusian Nuclear Power Plant will amount to 2400 MW. In addition, modern requirements for the regulation of the frequency and flows of active electric power in the power system have been tightened: the time to reach the half value of the required power alteration should be 10 seconds within the normal and emergency reserves; the time to reach the full value of the required power alteration should be 30 seconds within the range of the normal reserve and 2 minutes – within the range of the emergency reserve. With this regard, increasing the efficiency of the units operating in the variable part of the electric load schеdule by the use of modern methods of calculation of parameters of the dynamic adjustment of the regulating devices of ACSPU becomes an urgent problem. The methodology of parametric optimization of the typical ACSPU that make it possible to improve the quality of power regulation and the pressure of the superheated steam upstream of the turbine is presented. The described technique is illustrated by the results of computer simulation of transient processes in the system when the task and internal disturbances are worked out, which confirm the correctness of the proposed technique in comparison with the known methods of optimization of the typical ACSPU.